O corpo está no contrato? Estudo sobre as ocorrências de assédio sexual contra mulheres jornalistas nas redações de Imperatriz - AMORIM, Janaina lopes de (2021)
This one deals with the sexual issue by women journalists who work in Imperatriz (BAD). The study aims to understand how sexual harassment journalists takes place in the second largest city in Maranhão, as well as identifying the practices of discrimination in the work routine, starting from the frequent routine in which this violence is other cities, as shown by previous national studies such as Abraji (2017) that covers the cities of Brasília, Porto Alegre, Rio de Janeiro and São Paulo, that of the researcher Portela (2018), held in Curitiba, and Lima, Santos and Tavares (2019), in Balsas. Didactically, the question you are studying is: how does this sexual harassment guide you? women journalists from Imperatriz manifests itself in the journalistic routine and what is its impact on these professionals? To account for this proposal, we opted for an empirical research with qualitative, anchored in open and in-depth interviews. The procedure of and data analysis was guided by the bases of Content Analysis, which consists of in a set of techniques that allows the interpretation of communications, composed of the phases of description, interpretation and inference (BARDIN, 1977; PUGLISI, FRANCO, 2005). all in all, 19 journalists were heard from a universe of vehicles that are part of the universe of the study, which comprises TV and radio newsrooms and a news portal. ONE reasoning that dialogues with the research was based on authors such as Safiotti (1987;1976), Louro (2011), Fukuda (2012) and Butler (2003). Among the notes found is that harassment is part of journalists' routine and that this violence impacts both for the victims' health and for their careers. Indirectly the violence ends also affecting the quality of the material made available to the public. The study identified further, that Imperatriz, despite being a medium-sized city in the interior of Maranhão, has a similar reality in relation to the frequency and characteristics of harassment in the other country cities. It also showed that most of the harassers are men who occupy management position or have some position considered to be of social support. This aggression takes place at all stages of the work, covering external and internal environments, both face-to-face and through online social media. Furthermore, this violent act has both for professionals, who go through a situation of illness, and for the routine journalistic, as women switch topics, avoid sources and drop coverage to avoid contact with the harassers. And, although it does not end the harassment issue, when presenting the results and particularities of a city in the countryside, in the Northeast of the country, the research intends to contribute to broadening perspectives on gender relations and harassment against women in the journalism job market, to collaborate to show that this problem exists and its seriousness and thus draw attention to the importance of the debate on the subject.